The Centre of Attention: A Powerful Radio Galaxy Pinpoints a Near-infrared-dark Protocluster at z ∼ 3.9 - A. J. Hedge; N. Seymour; J. W. Broderick; A. Gupta; J. Afonso; L. Ighina; M. Lehnert; G. Noirot; S. Shabala; D. Stern; R. J. Turner (The Astrophysical Journal)
We report the discovery of a z ∼ 3.9 protocluster identified from Atacama Large Millimeter/submillimeter Array Band 3 spectral scans of a bright radio source selected from the Galactic and Extragalactic All-sky Murchison Widefield Array (GLEAM) survey. Extended CO(4–3) and [C I ] ( ^3 P _1 → ^3 P _0 ) line emission was detected in GLEAM J005332−325630 confirming it to be a z = 3.879 powerful radio galaxy with luminosity L _500 MHz = 1.3 × 10 ^28 W Hz ^−1 . This source is part of a sample of candidate high-redshift radio galaxies with bright radio fluxes, S _150 MHz > 0.1 Jy, but host galaxies with K _s (AB) ≳ 23 mag. The molecular gas associated with the radio galaxy host has two kinematically separate components, likely infalling and indicative of a recent interaction or merger with another galaxy. One 100 GHz continuum source ∼120 pkpc away is found to have both CO(4–3) and [C I ] ( ^3 P _1 → ^3 P _0 ) emission lines and a further five protocluster members are identified from CO(4–3) emission alone, all at a similar redshift (Δ v < 700 km s ^−1 ) and within a radius of $1.^{′} 1$ . Using photometry from the High Acuity Widefield K -band Imager K _s band and the Dark Energy Survey g , r , i , z , and Y bands, we find this protocluster harbours a rare, optically dark, very massive M _* ∼ 10 ^12 M _⊙ galaxy. Comparisons with the TNG300 cosmological simulation puts this galaxy in a dark matter (DM) halo of M _DM ∼ 3 × 10 ^13 M _⊙ , which will evolve into a Coma-like DM halo ( M _DM ∼ 10 ^15 M _⊙ ) by the present day.